iBrain
contestada

Use function notation to write a recursive formula to represent the sequence: 3, 6, 12,...
f(n) = f(n − 1) + 3
f(n) = f(n - 1) + 2
f(n) = f(n-1).3
f(n) = f(n-1)2

Respuesta :

Answer:

f(n)=f(n-1)×2

Step-by-step explanation:

The previous term is being multiplied by 2 to get a term.

First term is 3.

Second term is 3×2=6.

Third term is 6×2=12.

....

nth term is f(n-1)×2.

Note: f(n-1) is just the term before f(n).

f(n)=f(n-1)×2 with f(1)=3 is the recursive form for this sequence.

Answer:

f(n) = f(n − 1) ⋅ 2

Step-by-step explanation:

I took the test on flvs and got it right.

100% Guaranteed Correct :)

, Hope this helps

Have a great day!!